PENERAPAN METODE AL-HUSNA DALAM PEMBELAJARAN MEMBACA AL-QUR’AN LINGKAR QUR’AN AL-IKHLAS DI MASJID MUNIROH TAHUN AJARAN 2022/2023 - Dian Vita Loka; Mukhlis Fathurrahman; Sulistyowati (MAMBA'UL 'ULUM, 2023)
The aim of this study was to investigate the implementation of the Al-Husna method for teaching hijaiyah letters. The research employed a descriptive qualitative approach, utilizing data from observations, interviews, and documentation. The collected data were analyzed using the Miles and Huberman model, which involved data collection, data reduction, presentation, and drawing conclusions. The findings of the study indicate that the Al-Husna method facilitates Quranic reading by making it easier, practical, systematic, and aligned with the teachings of Prophet Muhammad (SAW) and his companions. The method incorporates Ottoman script as a basis for learning and authenticating the letters. The application of the Al-Husna method in the Al-Ikhlas Qur'an Circle at Muniroh Mosque consists of three stages: preparation, implementation, and assessment. The preparatory stage involves organizing study circles. The subsequent stage focuses on introducing hijaiyah letters through a sequential system, scanning and keywords, and teaching letter formation. The final stage entails evaluating students' learning outcomes using mutaba'ah cards. In conclusion, the Al-Husna method proves beneficial for children, as evidenced by a 75% success rate in Quranic reading and comprehension of hijaiyah letters at an early age.